2002
DOI: 10.1002/bip.10157
|View full text |Cite
|
Sign up to set email alerts
|

High resolution NMR analysis of the seven transmembrane domains of a heptahelical receptor in organic‐aqueous medium

Abstract: The NMR properties of seven peptides representing the transmembrane domains of the alpha-factor receptor from Saccharomyces cerevisiae were examined in trifluoroethanol/water (4:1) at 10 to 55 degrees C. The parameters extracted indicated all peptides were helical in this membrane mimetic solvent. Using chemical shift indices as the criterion, helicity varied from 64 to 83%. The helical residues in the peptides corresponded to the region predicted to cross the hydrocarbon interior of the bilayer. A study of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
4

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 51 publications
(55 reference statements)
0
23
0
4
Order By: Relevance
“…This approach builds on prior efforts by multiple research groups to characterize GPCR loop sequences in organic and aqueous solutions both without [16][17][18][19] and with 18,20 internal structural constraints. NMR structures have been determined for various segments of GPCRs including TMs of the a-factor receptor in 80% trifluoroethanol (TFE) 21 ; the N-terminus, 22 first extracellular loop 23 and third cytoplasmic loop 24 of the parathyroid hormone receptor (PTH1R) in aqueous solution or SDS/DPC micelles; the third intracellular loop of the human cannabinoid 1 receptor (CB1) in SDS micelles 16 ; and bovine rhodopsin loops in dimethylsulfoxide (DMSO). 17 Structural studies on unconstrained peptide mimics of GPCR loops indicated that the native conformation in the intact protein cannot be obtained in aqueous solution and SDS micelles.…”
Section: Introductionmentioning
confidence: 99%
“…This approach builds on prior efforts by multiple research groups to characterize GPCR loop sequences in organic and aqueous solutions both without [16][17][18][19] and with 18,20 internal structural constraints. NMR structures have been determined for various segments of GPCRs including TMs of the a-factor receptor in 80% trifluoroethanol (TFE) 21 ; the N-terminus, 22 first extracellular loop 23 and third cytoplasmic loop 24 of the parathyroid hormone receptor (PTH1R) in aqueous solution or SDS/DPC micelles; the third intracellular loop of the human cannabinoid 1 receptor (CB1) in SDS micelles 16 ; and bovine rhodopsin loops in dimethylsulfoxide (DMSO). 17 Structural studies on unconstrained peptide mimics of GPCR loops indicated that the native conformation in the intact protein cannot be obtained in aqueous solution and SDS micelles.…”
Section: Introductionmentioning
confidence: 99%
“…Mesmo em relação a fragmentos transmembranares, grupos como o de Naider et aI. (64)(65)(66)(67) mostraram a importância de se estudar domínios de…”
Section: Ij\unclassified
“…(64)(65)(66)(67) observou que alguns dos fragmentos transmembranares não adotam conformação a-helicoidal nem mesmo em TFE. É possível que isso também seja verdade para outros receptores.…”
Section: Ij\unclassified
See 2 more Smart Citations